2017
DOI: 10.1016/j.joca.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic cartilage repair scoring of defect fill, integration and total points correlate with corresponding items in histological scoring systems – a study in adult sheep

Abstract: Major individual morphological categories "defect fill" and "integration", and "total points" of macroscopic scoring systems correlate with their corresponding categories in elementary and complex histological scoring systems. Thus, macroscopy allows to precisely predict key histological aspects of articular cartilage repair, underlining the specific value of macroscopic scoring for examining cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
(25 reference statements)
0
17
1
Order By: Relevance
“…It is important to determine standardized methods of assessing outcomes relevant to cartilage repair. Several studies reported improvements in the macroscopic appearance of cartilage; while macroscopic appearance scoring is predictive of histological scoring (Goebel et al, 2017), it is unclear how this correlates with functional improvements. The three studies that used collagenase to induce cartilage loss, often termed collagenase induced OA (CIOA) models, assessed the highly clinically relevant outcomes of pain behavior, with both reporting reduction from early stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine standardized methods of assessing outcomes relevant to cartilage repair. Several studies reported improvements in the macroscopic appearance of cartilage; while macroscopic appearance scoring is predictive of histological scoring (Goebel et al, 2017), it is unclear how this correlates with functional improvements. The three studies that used collagenase to induce cartilage loss, often termed collagenase induced OA (CIOA) models, assessed the highly clinically relevant outcomes of pain behavior, with both reporting reduction from early stages.…”
Section: Discussionmentioning
confidence: 99%
“…According to the initial report of this trial, the average and the size variation of the repair sites (2.4-2.6 cm 2 ; SD 1.2-1.0) were significantly smaller than in our material. 18 In an animal study, Goebel et al 20 analyzed macroscopically the performance of different repair tissue scoring systems, including the ICRS and the OAS scores. These investigators used material of standard-sized (4 × 8 mm) lesions in 38 medial femoral condyles of Merino sheep who were sacrificed 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reliability of both scores to evaluate repair tissue quality in larger cartilage lesions is unknown. Furthermore, previous validation studies have shown limitations in score performance, but the reasons for these deficiencies remain unclear . Because the ICRS and OAS scores are used to assess the outcome of cartilage repair in various types of cartilage lesions, it is important to understand how the lesion characteristics might affect the reliability of both scores and what reasons might explain the previously observed limitations in score performance.…”
mentioning
confidence: 99%
“…Previous studies have shown excellent correlation and reliability between macroscopic and histological results when using the ICRS score. 16,47 Thus, we decided to use it to assess macroscopic regeneration. Correlation of macroscopic ICRS scoring to histological results has been validated only for assessment of cartilage repair with microfracture technique, 16 yet it is well known that microfracture does not lead to hyaline cartilage but rather leads to fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…16,47 Thus, we decided to use it to assess macroscopic regeneration. Correlation of macroscopic ICRS scoring to histological results has been validated only for assessment of cartilage repair with microfracture technique, 16 yet it is well known that microfracture does not lead to hyaline cartilage but rather leads to fibrous tissue. 13 Evaluation of cartilage repair with more sophisticated tissue engineering therapies may require further variables to be evaluated, such as those proposed by Goebel et al 16 In contrast with the ICRS score, Goebel's score evaluates 5 variables: defect fill and surface (also present in the ICRS score), color, presence of blood vessels, and degeneration of adjacent articular cartilage.…”
Section: Discussionmentioning
confidence: 99%